Cultural Heritage of Punjab: A Shift in Outlook and Output—A Case Study of the Historical Town of Sirhind - Mallika Sharma* (International Journal of Architectural Design and Planning, 2023)
Cultural heritage is an expression of ways of living developed by a community and passed on from generation to generation. This could be the tangible assets, such as buildings, monuments, archaeological sites, artifacts, landscape, and intangible assets such as oral traditions, folklore, language, and knowledge. Though all these can be viewed, analyzed, studied separately, they cannot be experienced as standalone entities. The understanding of our cultural heritage is fragmented and the need is to go beyond the traditional view of cultural heritage as material objects requiring conservation and preservation. The methodology for the study has been exploratory with reviewing literary sources. Offering a broad overview of what entails cultural heritage, the purpose is to initiate a dialogue on how, in the context of Punjab, it could be best understood and experienced so as to give justice to the richness it has to offer while understanding that this will always be an on-going process. The historical city of Sirhind has been taken as a case example, which for all of the vicissitudes of its history, continues to showcase a unique case of cultural heritage assets.
Keywords: Culture; Punjab; architecture; conservation; cultural heritage; history; landscape; sacred